Warren, Max. Interview about growing up in New Perlican and the goats in the community. - Barrett, Terra (2017)
Terra Barrett of the Heritage Foundation of Newfoundland and Labrador interviews Max Warren about growing up in New Perlican, and his goat memories for The Goats of New Perlican Oral History Roadshow Project in partnership with Heritage New Perlican.